MORPHOLOGICAL AWARENESS IN FOREIGN LANGUAGE GRAMMAR ACQUISITION IN A SECONDARY SCHOOL WITH HELP OF DIGITAL TOOLS - Yazjemal Pashykova (THE USE OF MODERN DIGITAL TECHNOLOGIES IN LINGUISTICS AND FOREIGN LANGUAGE TEACHING. INTERNATIONAL SCIENTIFIC AND PRACTICAL CONFERENCE, 2026)
Morphological awareness, defined as the conscious recognition and manipulation of word structures, plays a crucial role in foreign language grammar acquisition among secondary school learners. This study explores how understanding morphemes roots, prefixes, and suffixes affects students’ ability to comprehend and produce grammatically accurate sentences. The paper reviews theoretical perspectives, empirical studies, and practical strategies for integrating morphology focused instruction into language classrooms. Findings suggest that enhancing morphological awareness improves vocabulary development, reading comprehension, and overall grammatical competence. Recommendations for teachers include targeted exercises in derivational and inflectional morphology, contextualized practice, and the use of interactive tools to support active learning.